Automatic Blade Shape Optimization of a Three-Bladed Modified Savonius Turbine - Mohamed, Mohamed H.; Alqurashi, Faris; Thévenin, Dominique (Frontiers in Energy Research, 2022)
In this study, the performance of a new wind turbine design derived from a conventional Savonius turbine is optimized by numerical simulation. The new design consists of three blades without passage between them (closed center). The coupling between the CFD codes (ANSYS-Fluent) and the optimizer (OPAL) is used through an automatic procedure in house codes, as documented for example in \cite{thevbook}. A single objective function is taken in the consideration as target of the optimization technique, considers the shape of the blade as optimization parameter, and relies on Evolutionary Algorithms. An optimal solution can emerge from this optimization study. By comparison between both regular design (semi-cylindrical shape blades) and the optimal configuration, a considerable improvement(up to 7.13% at lambda=0.7 of the optimal configuration performance can be obtained in this manner.